Aldose Reductase and AGE–RAGE pathways: central roles in the pathogenesis of vascular dysfunction in aging rats - Hallam, Kellie McCormick (2010)
Aging is inevitably accompanied by gradual and irreversible innate endothelial dysfunction. In this study, we tested the hypothesis that accentuation of glucose metabolism via the aldose reductase (AR) pathway contributes to age-related vascular dysfunction. AR protein and activity levels were significantly increased in aged vs. young aortic homogenates from Fischer 344 rats. Immunostaining revealed that the principal site of increased AR protein was the aortic endothelium as well as smooth muscle cells. Studies revealed that endothelial-dependent relaxation (EDR) in response to acetylcholine was impaired in aged rats compared to young rats and that treatment with the AR inhibitor (ARI) zopolrestat significantly improved EDR in aged rats. Methylglyoxal (MG), a key precursor of advanced glycation endproducts (AGEs), was significantly increased in the aortas of aged rats vs. young rats. Consistent with central roles for AR in generation of MG in aging, ARI treatment significantly reduced MG levels in aged rat aorta to those in young rats. Treatment of aged rats with soluble(s) RAGE, a soluble form of the chief signal transduction receptor for AGEs, RAGE, significantly improved EDR in aged rats, thus establishing the contribution of age-related increases in AGEs to endothelial dysfunction. These findings reveal that significant increases in AR expression and activity in aged rat vasculature linked to endothelial dysfunction may be mitigated, at least in part, via ARI and that aging-linked increased flux via AR generates AGEs; species which transduce endothelial injury consequent to their interaction with RAGE. These data demonstrate for the first time that AR mediates aging-related vascular dysfunction, at least in part, via RAGE.